(untitled) (Research, Society and Development, 2021)
This article analyzes the population of organizations providing notary and registration services, (technical / administrative organization), under the terms of Article 1 of Law 6.015 / 73 and Article 1 of Law 8,935 / 94, designed to provide publicity, authenticity, effectiveness and security to the legal acts of the state of Bahia, in the lig.t of the theory of population ecology, in the union context of COVID-19. The research question raised is whether, in this population or community of organizations (the extrajudicial services), the imposition of regulatory normative acts in the face of the pandemic (sindemya) environment and the requirements for maintaining quality in the provision of services to society, led holders and interim to seek optimization in the use of scarce and uncertain resources and what or which resources are subject to optimization? The objective is to analyze how the types of organizations, within their populations of organizations of extrajudicial services, can use new combinations of resources present in the environment to survive, being this survival in order to fulfill the purposes of meeting the demands of society and provide return to the organization. The research was carried out in the state of Bahia, in 2020, elaborated in three stages: a) conceptual; b) characterization of the population and; c) comparative analysis of the actions taken. Therefore, even with stable systems, this population was destabilized by environmental factors, which escaped purely managerial reach. Disruptive changes in the union environment, exposed solid knowledge (in this case, the technical / legal), quickly demanding other knowledge (in this case the management and digital technologies).